ISOLASI DNA TOTAL IKAN SELAIS Ompok eugeneiatus (Vaillant 1893) DARI SUNGAI KAMPAR KIRI DAN INDRAGIRI HULU PROVINSI RIAU - ', Tasiah; Elvyra, Roza; Roslim, Dewi Indriyani (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
DNA isolation is a process to obtain pure DNA. The total DNA isolated includes nuclei and cytoplasm DNA (mitochondrial and chloroplast DNA). The total DNA can be used as stock for further genetic diversity analysis. Scientific information on genetic diversity of selais fish in Indonesia, particularly in Riau is still limited. One of the dominant species of selais fish in Riau is Ompok eugeneiatus. The research was conducted to obtain the total DNA of selais fish which can be used as a template DNA for genetic diversity analysis. The research had been conducted from December 2013 to May 2014 and the study site was located in Kampar Kiri and Indragiri Hulu rivers, Riau Province. Ten samples were isolated from each river. The DNA isolation process used isolation and purification kit (Qiagen DNeasy Blood & Tissue brand). The DNA isolation process was conducted based on the existing protocol. The total DNA were then migrated on 1% agarose gel and then visualized using UV transluminator. This research obtained the total DNA from each selais fish samples of Ompok eugeneiatus from the Kampar Kiri and Indragiri Hulu rivers with different quantity. The total DNA obtained were not fragmented.